Effectiveness of nootropic drugs with cholinergic activity in treatment of cognitive deficit: a review - Colucci L; Bosco M; Ziello AR; Rea R; Amenta F; Fasanaro AM (Dove Medical Press, 2012)
Luisa Colucci,1,2 Massimiliano Bosco,2 Antonio Rosario Ziello,1,2 Raffaele Rea,1,2 Francesco Amenta,1 Angiola Maria Fasanaro21Centro di Ricerche Cliniche, Telemedicina e Telefarmacia, Università di Camerino, Camerino, 2Unità Valutazione Alzheimer, Naples, ItalyAbstract: Nootropics represent probably the first “smart drugs” used for the treatment of cognitive deficits. The aim of this paper is to verify, by a systematic analysis of the literature, the effectiveness of nootropics in this indication. The analysis was limited to nootropics with cholinergic activity, in view of the role played by acetylcholine in learning and memory. Acetylcholine was the first neurotransmitter identified in the history of neuroscience and is the main neurotransmitter of the peripheral, autonomic, and enteric nervous systems. We conducted a systematic review of the literature for the 5-year period 2006–2011. From the data reported in the literature, it emerges that nootropics may be an effective alternative for strengthening and enhancing cognitive performance in patients with a range of pathologies. Although nootropics, and specifically the cholinergic precursors, already have a long history behind them, according to recent renewal of interest, they still seem to have a significant therapeutic role. Drugs with regulatory indications for symptomatic treatment of Alzheimer's disease, such as cholinesterase inhibitors and memantine, often have transient effects in dementia disorders. Nootropics with a cholinergic profile and documented clinical effectiveness in combination with cognate drugs such as cholinesterase inhibitors or alone in patients who are not suitable for these inhibitors should be taken into account and evaluated further.Keywords: cholinergic nootropics, cognitive function, dementia